2015
DOI: 10.1523/jneurosci.1001-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bexarotene-Activated Retinoid X Receptors Regulate Neuronal Differentiation and Dendritic Complexity

Abstract: Bexarotene-activated retinoid X receptors (RXRs) ameliorate memory deficits in Alzheimer's disease mouse models, including mice expressing human apolipoprotein E (APOE) isoforms. The goal of this study was to gain further insight into molecular mechanisms whereby ligand-activated RXR can affect or restore cognitive functions. We used an unbiased approach to discover genome-wide changes in RXR cistrome (ChIP-Seq) and gene expression profile (RNA-Seq) in response to bexarotene in the cortex of APOE4 mice. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 82 publications
7
63
0
Order By: Relevance
“…Brains from five female and three male mice of each genotype, all 7-10 months old, were removed and snap frozen as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brains from five female and three male mice of each genotype, all 7-10 months old, were removed and snap frozen as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis derives, in part, from evidence that the strongest correlate of cognitive impairment in AD is loss of synapses (3,4), with excitatory synapses onto dendritic spines particularly affected (5)(6)(7). Conversely, in cognitively normal individuals who nevertheless have substantial AD pathology, neuron number and synaptic markers are largely preserved (8).…”
Section: An Important Hypothesis In Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Probably through these mechanism agonists of PPAR-α may have a promising effect in a mouse model of aging-dependent cognitive impairments [37,38]. Moreover, it was previously reported that RXR activation increases dendritic complexity and branching of neurons and differentiation [39,40] but it seems now that PPAR-α plays a key role in these processes.…”
Section: Ppar-α and Its Role In Neurotransmission In The Brainmentioning
confidence: 99%
“…This effect was validated in a mouse model, demonstrating that following bexarotene treatment, both APOE3 and APOE4 mice had an increased number of neural progenitors in the dentate gyrus. Furthermore, bexarotene significantly improved the compromised dendritic structure in the hippocampus of APOE4 mice (Mounier et al, ). RNA‐Seq data showed an enrichment of Gene Ontology categories related to neuronal differentiation, neurite growth, and neuritogenesis in APOE4 mice treated with bexarotene.…”
Section: Retinoid X Receptorsmentioning
confidence: 99%
“…Interestingly, RNA‐Seq data demonstrated that bexarotene treatment affected Notch1 signalling known to be important in cell fate decisions in uncommitted proliferating cells and differentiation of immature neurons. Additional genes associated with changes in the Notch1 pathway following bexarotene treatment include Dlk1 , nerve growth factor receptor, and EGF receptor (Mounier et al, ). Most studies have demonstrated that adult neurogenesis, particularly in the dentate gyrus, improves behavioural deficits in rodents (reviewed in Lepousez, Nissant, & Lledo, ).…”
Section: Retinoid X Receptorsmentioning
confidence: 99%